1975
DOI: 10.2343/geochemj.9.7
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope studies on the origin and geological history of water and salts in the Lake Vanda area, Antarctica.

Abstract: Abstract-Possible origins of lake water, salts dissolved in water of a saline lake , Lake Vanda, those contained in cored sediments of the lake and those distributed on the ground surface in the adjacent area were investigated on the basis of the stable isotope compositions, 13C/12C, 180/160 and 34S/325 .The lake water is concluded to be neither marine nor volcanic in origin but surface fresh water such as glacial melt water, because of the low 8180 values ranging from -30.3 to -31.9%0. On the other hand, sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…Lake Bonney in Taylor Valley and Lake Vanda in Wright Valley retain hypersaline deep waters with salinities above 100 g/kg (L Bonney, west lobe and L Vanda) and 200 g/kg (L Bonney, east lobe). Based on the chemical and isotopic profiles of these lakes, several investigators (Hendy et al 1977;Lyons et al 1998a;Matsubaya et al 1979;Nakai et al 1975;Ragotzkie and Friedman 1965;Torii and Yamagata 1981) interpreted that the saline, deep waters were formed as a result of the evaporation of lakes to small hypersaline icefree ponds or perhaps to near dryness during a colder and drier climate in the past. Lake Bonney is at least 300-ky old and Lyons et al (2005) suggested that the hypolimnia of Lake Bonney are remnants of a marine fjord of Miocene time.…”
Section: Mcmurdo Dry Valleysmentioning
confidence: 99%
“…Lake Bonney in Taylor Valley and Lake Vanda in Wright Valley retain hypersaline deep waters with salinities above 100 g/kg (L Bonney, west lobe and L Vanda) and 200 g/kg (L Bonney, east lobe). Based on the chemical and isotopic profiles of these lakes, several investigators (Hendy et al 1977;Lyons et al 1998a;Matsubaya et al 1979;Nakai et al 1975;Ragotzkie and Friedman 1965;Torii and Yamagata 1981) interpreted that the saline, deep waters were formed as a result of the evaporation of lakes to small hypersaline icefree ponds or perhaps to near dryness during a colder and drier climate in the past. Lake Bonney is at least 300-ky old and Lyons et al (2005) suggested that the hypolimnia of Lake Bonney are remnants of a marine fjord of Miocene time.…”
Section: Mcmurdo Dry Valleysmentioning
confidence: 99%
“…Salt residues from wind-blown sprays are a widespread phenomenon on Antarctic boulders and within soils. Carbon and oxygen isotopic measurements (Nakai et al, 1975) of surficial calcite coatings on rocks from the Wright Dry Valley region of Antarctica display a range in Ol3C (-14.4 to + 17.60/00) and 0 18 0 (-0.4 to + 22.30/00), with different boulders from the same locality showing a large variation. The total range easily encompasses the values obtained for the first generation of bicarbonates from LEW 85320 measured by this study and Gooding et al (1988b), and its local inconsistency may explain the discrepancy between the results obtained by the two sets of investigators.…”
Section: Discussionmentioning
confidence: 99%
“…2) On the contrary, it may be argued that Antarctic meteorites are subjected to terrestrial carbonate contamination with heavy S13C by weathering (e.g., Velbel et al, 1991;Miyamoto, 1991). Most S13C values of surface carbonate on terrestrial Antarctic materials are lower (-14.4 to +17.6%o; Nakai et al, 1975) than those of indig enous carbonate in carbonaceous chondrites (+20 to 60%o, Clayton, 1963;Grady et al, 1988). Grady et al (1988) (Table 2).…”
Section: Differences In Carbon Content and Isotope Ratio Between Antamentioning
confidence: 99%